What is online financial management about? A content analysis on popular post by online financial channels on Instagram - Leong, Zhi Lun (2022)
Purpose: This research used content analysis to analyse the popular content posted by Malaysian Online Financial Channels on social media (Instagram). The general ideas of the content posted by the online financial channels was determined via categorisation and descriptive statistics which were analysed using SPSS. The post image and caption were analysed separately. Design/Methodology/Approach: 16 online financial channels own by Malaysian with status as micro influencer were chosen. This research was carried out from 1st January 2020 to 31st December 2021. The top 9 post in each year from each online financial channel were chosen. A total 288 samples were collected. It is categorised into 12 different categories determined for this study. The method of content analysis has utilised both quantitative and qualitative method. Findings: This research showed that the dominant content for image category was promotional content. Whereas for the captions, interactive content category was the dominant category. Research Implications: Online financial channels used contents that has interactive content to attract user and lead them to take more action i.e., sign up for webinar. This is similar to the AIDA (Attention, Interest, Desire, and Action) model. Besides, online financial channels found Instagram as an effective platform for them to promote something.